Inflow Parameter Effects on Wind Turbine Tower Cyclic Loading. Issue 5 (October 2014) - Smith, Jamie C.; Carriveau, Rupp; Ting, David S-K
Wind turbine towers are fatigue-critical structures subjected to a variety of atmospheric wind regimes at onshore installations. At a commercial wind farm in Southwestern Ontario, the structural steel supporting tower of a multi-megawatt horizontal-axis turbine has been instrumented with a fiber Bragg grating strain gauge array. A nearby meteorological mast allows wind conditions to be classified on the basis of horizontal turbulence intensity and vertical wind shear. Data has been collected over a measurement campaign spanning multiple months, and a sample of the tower's cyclic loading history has been compiled. Comparisons are drawn between accumulated hourly loading cycle spectra for operation across different upwind inflow parameters.